Enhancing cinnamon essential oil activity by nanoparticle encapsulation to control seed pathogens - Bravo Cadena, M; Preston, G; Van Der Hoorn, R; Flanagan, N; Townley, H; Thompson, I (Elsevier, 2018)
Natural biocides, such as cinnamon (Cinnamomum zeylanicum) bark essential oil, have enormous potential as antimicrobials but are limited by their volatility and rapid degradation. To counteract this and to prolong the efficacy of the biocide, cinnamaldehyde (CNAD, the main bioactive compound of cinnamon essential oil) was encapsulated into mesoporous silica nanoparticles (MSNPs). The synthesised CNAD-MSNPs can be used to tackle the issue of global crop loss; every year, more than 40% of global food production (estimated at $500 billion USD) is lost to diseases. This is despite the annual use of over two million tonnes of pesticides. To address seed borne diseases, CNAD-MSNPs were incorporated into a sodium alginate seed coating. As a proof of concept, this system was tested against Pseudomonas syringae pv. pisi, the causative agent of pea bacterial blight, and demonstrated to increase the number of symptomless plants by 143.58% twenty days after sowing. Additionally, the concentration of CNAD present in the alginate coating was estimated to be <0.0000034% (v/v); up to 90,000-fold lower than concentrations of free cinnamon oil previously reported to control some bacterial diseases. Furthermore, alginate-treated seeds germinated faster than control plants, and were physiologically similar, demonstrating the dual benefit of this treatment. To the best of our knowledge, this is the first study to exploit the combined properties of essential oils, alginate and MSNPs as a seed treatment to control bacterial phytopathogens. Moreover, this study proved that the antimicrobial activity of plant products can be significantly enhanced by MSNP encapsulation, allowing volatile biocides, such as essential oils, to be used effectively at very low concentrations to treat and prevent microbial diseases in crops.